2015
DOI: 10.1016/j.physbeh.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The nature of impairments of memory in patients with end-stage renal disease (ESRD)

Abstract: Possible impairments of memory in end-stage renal disease (ESRD) were investigated in two experiments. In Experiment 1, in which stimulus words were presented visually, participants were tested on conceptual or perceptual memory tasks, with retrieval being either explicit or implicit. Compared with healthy controls, ESRD patients were impaired when memory required conceptual but not when it required perceptual processing, regardless of whether retrieval was explicit or implicit. An impairment of conceptual imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…In laboratory studies of cognition, ESRD has been associated with multiple impairments (Hart & Kreutzer, 1988), for example, of visual attention (Etgen et al, 2009), executive functioning (Jassal, Devins, Chan, Bozanovic, & Rourke, 2006) and psychomotor speed (Griva et al, 2003). In addition, various aspects of memory have been shown to be impaired: verbal and visual memory (Elias et al, 2009;Kurella, Chertow, Luan, & Yaffe, 2004), working memory (Buchman et al, 2009), episodic memory (Thornton, Shapiro, Deria, Gelb, & Hill, 2007) and conceptual memory (Jones et al, 2015b). However, it is uncertain whether patients are aware of these impairments, and to what extent they impact on everyday life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory studies of cognition, ESRD has been associated with multiple impairments (Hart & Kreutzer, 1988), for example, of visual attention (Etgen et al, 2009), executive functioning (Jassal, Devins, Chan, Bozanovic, & Rourke, 2006) and psychomotor speed (Griva et al, 2003). In addition, various aspects of memory have been shown to be impaired: verbal and visual memory (Elias et al, 2009;Kurella, Chertow, Luan, & Yaffe, 2004), working memory (Buchman et al, 2009), episodic memory (Thornton, Shapiro, Deria, Gelb, & Hill, 2007) and conceptual memory (Jones et al, 2015b). However, it is uncertain whether patients are aware of these impairments, and to what extent they impact on everyday life.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative studies investigating the impact of ESRD have provided substantial, useful data; however, because one of the aims of qualitative research was to provide understanding of the meanings and interpretations of behaviour within the specific sample under study, it is of value to conduct further qualitative research with additional samples in order to establish the extent to which similar themes emerge and new themes are revealed. In this study, we were particularly interested in the fluctuations in cognitive abilities caused by HD, reported to us by patients in quantitative studies of cognition (Jones, Butler, Harris, & Vaux, ; Jones, et al., ). In addition, this study aims to provide an understanding of the patient experience in the UK NHS.…”
Section: Introductionmentioning
confidence: 99%
“…We have herein reported memory disorders and renal disease just in one patient (2%). Jones et al [65], studied the nature of impairments of memory in patients with End-Stage Renal Disease (ESRD). They concluded that the type of processing required by the task (conceptual vs. perceptual) is more important than the type of retrieval (explicit vs. implicit) in memory failures in ESRD patients, perhaps because temporal brain regions are more susceptible to the effects of the illness than are posterior region.…”
Section: Memory Disorders and Renal Diseasesmentioning
confidence: 99%
“…During retrieval, they were presented with a series of six category names and had to recall and report any words from the earlier list which belonged in that category (full details of the task provided by Jones et al). 39 Participants also completed the Mini Mental State Examination (MMSE), 40 to screen for moderate to severe cognitive impairment; the Instrumental Activity of Daily Living (IADL), 41 a self-report questionnaire to assess independence; the National Adult Reading Test (NART), 42 a performance-based questionnaire assessing premorbid intelligence; and the Bond-Lader Mood Assessment Scale, 43 a measure of subjective mood.…”
Section: Stimuli and Materialsmentioning
confidence: 99%